Comprehension of Generalized Conversational Implicatures by Children With and Without Autism Spectrum Disorder - Pastor-Cerezuela, Gemma; Tordera Yllescas, Juan C.; González-Sala, Francisco; Montagut-Asunción, Maite; Fernández-Andrés, María-Inmaculada (Frontiers in Psychology, 2018)
This study evaluates the comprehension of generalized conversational implicatures (GCI) in children with and without autism spectrum disorder (ASD), using a GCI test constructed based on the Levinson model, which distinguishes between three types of implicatures: type Q (or scalar: “what is not referred to does not occur”); type I (“by default, it is not necessary to say what can be assumed”); and type M (“if someone is expressing something in a not very simple or marked way, it is because s/he is describing a situation that is not very typical, frequent, or prototypical”). In addition to the ASD group (n = 22), two comparison groups were utilized: a group matched on chronological age with the ASD group, but with a higher linguistic age (TCD group, n = 22), and a group matched on linguistic age with the ASD group, but with a lower chronological age (TLD group, n = 22). In all cases, linguistic age was assessed with the Peabody test. The performance of the three groups on the GCI test was compared (overall and on each type of implicature), and performance on the three types of implicature was compared within each group. The ASD group obtained worse performance than the other two groups, both overall and for each implicature type, without also obtaining differences in performance on the three implicature types. The TCD group obtained better performance than the TLD group on overall performance, but not on each implicature type, and both groups obtained lower performance on the type M heuristics than on the type I. Based on these results, the children with ASD in our study presented limitations in the comprehension of the three types of GCI, but it was not possible to obtain evidence for an inferential continuum of the three types of GCI. However, in the two typical development groups, this evidence was obtained, leading us to propose an inferential continuum model based on the different levels of dependence on the context of each of the three types of implicatures, with type M implicatures being more contextually dependent.